Mapping impressionist painting in transnational contexts
1 online resource (xv, 240 pages)
Keywords: "This book offers microhistories related to the transnational circulations of impressionism in the late nineteenth and early twentieth centuries. The contributors rethink the role of "French" impressionism in shaping these iterations by placing France within its global and imperialist context and arguing that impressionisms might be framed through the mobility studies' concept of "constellations of mobility." Artists engaging with impressionism in France, as in other global contexts, relied on, responded to, appropriated and resisted elements of form and content based on fluid and interconnected political realities and market structures. Written by scholars and curators, the chapters demand reconsideration of impressionism as a historical construct and the meanings assigned to that term. This project frames future discussion in art history, cultural studies, and global studies on the politics of appropriating impressionism"--